Guidance of thalamocortical innervation. - Molnár, Z; Blakemore, C (1995)
We propose that a sequence of individually simple mechanisms influences the pattern of thalamocortical innervation, which itself contributes to the determination of regional differentiation of the neocortex. In co-culture, the cortex appears to exert a remote growth-promoting influence on thalamic axons from E15, becomes growth-permissive to axon invasion at about E20 and expresses a stop signal, causing termination in layer IV, from P2-3. This cascade of cortical signals may determine the timing of events in vivo. However, any part of the thalamus will innervate any region of the developing cortex in culture, without obvious preference, suggesting that the topographic distribution of thalamic fibres in vivo does not depend on regional chemospecificity. The initial extension of axons from the cortical preplate and the thalamus starts at about E14, and the topography of both may be influenced by their temporal sequences of outgrowth (chronotopy). The axon arrays meet in the basal telencephalon, after which the preplate scaffold may guide thalamic axons and ensure both their 'capture' within the subplate layer and the establishment of the waiting period. The unusual pattern of innervation in the Reeler mutant mouse supports the hypothesis that thalamic axons grow over preplate fibres to find the waiting compartment.